2024
DOI: 10.3389/fphar.2023.1266311
|View full text |Cite
|
Sign up to set email alerts
|

Role of ATG7-dependent non-autophagic pathway in angiogenesis

Jinxiang Chen,
Yu Liang,
Shaorun Hu
et al.

Abstract: ATG7, one of the core proteins of autophagy, plays an important role in various biological processes, including the regulation of autophagy. While clear that autophagy drives angiogenesis, the role of ATG7 in angiogenesis remains less defined. Several studies have linked ATG7 with angiogenesis, which has long been underappreciated. The knockdown of ATG7 gene in cerebrovascular development leads to angiogenesis defects. In addition, specific knockout of ATG7 in endothelial cells results in abnormal development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…However, the extent to which this is necessary in order to firmly prove causality should not be underestimated. The reason for this is firstly that, as opposed to what was assumed upon their initial identification in the 1990s, most, if not all, ATG proteins have non-autophagic cellular functions ( Yousefi et al, 2006 ; Gan and Guan, 2008 ; Baisamy et al, 2009 ; Hanson et al, 2010 ; DeSelm et al, 2011 ; Chung et al, 2012 ; Lee et al, 2012 ; Velikkakath et al, 2012 ; Maskey et al, 2013 ; Elgendy et al, 2014 ; Rohatgi et al, 2015 ; Chen et al, 2016 ; Joo et al, 2016 ; Joshi et al, 2016 ; Kaizuka and Mizushima, 2016 ; Nunes et al, 2016 ; Yang et al, 2016 ; Guo et al, 2017 ; Ramkumar et al, 2017 ; Wang and Kundu, 2017 ; Cadwell and Debnath, 2018 ; Saleiro et al, 2018 ; Galluzzi and Green, 2019 ; Hu et al, 2020 ; Lindner et al, 2020 ; Wu et al, 2020 ; Fang et al, 2021 ; Li et al, 2021 ; Mailler et al, 2021 ; Nieto-Torres et al, 2021 ; Sun et al, 2021 ; Zhang et al, 2022a ; Hamaoui and Subtil, 2022 ; Rajak et al, 2022 ; Chen et al, 2023 ; Deng et al, 2023 ; Liang et al, 2023 ; Wang et al, 2023 ; Tedesco et al, 2024 ; Tran et al, 2024 ; Yoon et al, 2024 ) that are likely to influence the cellular/phenotypic effects that are observed upon their knockdown, knockout or overexpression, and many of these functions affect pathways that are highly relevant to cancer. Therefore, in order to infer causality, the same cellular/phenotypic effect must be observed upon interference with a number of different ATGs.…”
Section: Discussion—limitations Of Current Studies Main Challenges An...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent to which this is necessary in order to firmly prove causality should not be underestimated. The reason for this is firstly that, as opposed to what was assumed upon their initial identification in the 1990s, most, if not all, ATG proteins have non-autophagic cellular functions ( Yousefi et al, 2006 ; Gan and Guan, 2008 ; Baisamy et al, 2009 ; Hanson et al, 2010 ; DeSelm et al, 2011 ; Chung et al, 2012 ; Lee et al, 2012 ; Velikkakath et al, 2012 ; Maskey et al, 2013 ; Elgendy et al, 2014 ; Rohatgi et al, 2015 ; Chen et al, 2016 ; Joo et al, 2016 ; Joshi et al, 2016 ; Kaizuka and Mizushima, 2016 ; Nunes et al, 2016 ; Yang et al, 2016 ; Guo et al, 2017 ; Ramkumar et al, 2017 ; Wang and Kundu, 2017 ; Cadwell and Debnath, 2018 ; Saleiro et al, 2018 ; Galluzzi and Green, 2019 ; Hu et al, 2020 ; Lindner et al, 2020 ; Wu et al, 2020 ; Fang et al, 2021 ; Li et al, 2021 ; Mailler et al, 2021 ; Nieto-Torres et al, 2021 ; Sun et al, 2021 ; Zhang et al, 2022a ; Hamaoui and Subtil, 2022 ; Rajak et al, 2022 ; Chen et al, 2023 ; Deng et al, 2023 ; Liang et al, 2023 ; Wang et al, 2023 ; Tedesco et al, 2024 ; Tran et al, 2024 ; Yoon et al, 2024 ) that are likely to influence the cellular/phenotypic effects that are observed upon their knockdown, knockout or overexpression, and many of these functions affect pathways that are highly relevant to cancer. Therefore, in order to infer causality, the same cellular/phenotypic effect must be observed upon interference with a number of different ATGs.…”
Section: Discussion—limitations Of Current Studies Main Challenges An...mentioning
confidence: 99%
“…However, before concluding this, it is imperative to examine the effects of depletion of several other ATGs, as well as their effect in different models of prostate cancer. It is important to note that ATG7 has several non-autophagic functions ( DeSelm et al, 2011 ; Lee et al, 2012 ; Chen et al, 2023 ; Deng et al, 2023 ), and in relation to this, an alternative explanation for the delayed development and growth of the Pten deficiency-induced mouse prostate tumours mentioned above ( Santanam et al, 2016 ), could for instance, be related to the autophagy-independent effect that ATG7 has upon binding to the tumour suppressor TP53, which results in enhanced apoptotic cell death in the absence of Atg7 ( Lee et al, 2012 ). It should also be noted that prostate cancer has not been associated with alterations in ATG7 expression or function.…”
Section: Autophagy In Prostate Carcinogenesismentioning
confidence: 99%